2019
DOI: 10.3390/v11030216
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of Rhinovirus C in Differentiated Immortalized Human Airway HBEC3-KT Epithelial Cells

Abstract: Rhinoviruses (RVs) are classified into three species: RV-A, B, and C. Unlike RV-A and -B, RV-C cannot be propagated using standard cell culture systems. In order to isolate RV-Cs from clinical specimens and gain a better understanding of their biological properties and pathogenesis, we established air–liquid-interface (ALI) culture methods using HBEC3-KT and HSAEC1-KT immortalized human airway epithelial cells. HBEC3- and HSAEC1-ALI cultures morphologically resembled pseudostratified epithelia with cilia and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Others reported kinocilia on the apical surface of 3D tissue models on transwell inserts, Matrigel, or collagen gels using HBEC3-KT. 11,19,26 However, only little information on cilia functionality and surface coverage has been available. The SIS shows a connective tissue-like architecture made of mostly collagen and elastin.…”
Section: Discussionmentioning
confidence: 99%
“…Others reported kinocilia on the apical surface of 3D tissue models on transwell inserts, Matrigel, or collagen gels using HBEC3-KT. 11,19,26 However, only little information on cilia functionality and surface coverage has been available. The SIS shows a connective tissue-like architecture made of mostly collagen and elastin.…”
Section: Discussionmentioning
confidence: 99%
“…Abbreviations used GINA: Global Initiative for Asthma RV: Rhinovirus were previously able to identify species-specific antibody responses to RV-C-derived peptides, a species that has been difficult to propagate. 18 For the latter reason, we also know less about pathogenic differences between RV-A and RV-C strains in the etiology of asthma exacerbations because no infection models for RV-C are available. 19,20 However, it has been found that early multiple allergic sensitization in the first years of life is an important predictor of asthma.…”
Section: Follow-up Visitmentioning
confidence: 99%
“…The continuous invasion and high diversity of rhinoviruses have been observed [ 138 ]. Rhinovirus activity has been detected in countries of all continents: Spain [ 139 ], Brazil [ 140 , 141 , 142 ], Argentina [ 143 ], France [ 125 ], Italy [ 10 , 144 ], the United Kingdom [ 116 ], Russia [ 145 ], Finland [ 146 , 147 ], Canada [ 148 ], the US [ 3 , 102 , 137 , 149 , 150 , 151 ], Australia [ 152 ], Vietnam [ 153 ], China [ 154 , 155 ], Hong Kong [ 156 ], Japan [ 157 ], Burundi [ 158 ], KwaZulu-Natal (a province of South Africa) [ 159 ], Tanzania [ 90 ], and many others, including Antarctica [ 160 ].…”
Section: Epidemiologymentioning
confidence: 99%